Persistent T Cell Repertoire Perturbation and T Cell Activation in HIV After Long Term Treatment - Turner, Carolin T.; Brown, James; Shaw, Emily; Uddin, Imran; Tsaliki, Evdokia; Roe, Jennifer K.; Pollara, Gabriele; Sun, Yuxin; Heather, James M.; Lipman, Marc; Chain, Benny; Noursadeghi, Mahdad (Frontiers in Immunology, 2021)
Objective: In people living with HIV (PLHIV), we sought to test the hypothesis that long term anti retroviral therapy restores the normal T cell repertoire, and investigate the functional relationship of residual repertoire abnormalities to persistent immune system dysregulation. Methods: We conducted a case-control study in PLHIV and HIV negative volunteers, of circulating T cell receptor repertoire and whole blood transcriptomes by RNA sequencing, complemented by metadata from routinely collected health care records. Results: T cell receptor sequencing revealed persistent abnormalities in the clonal T cell repertoire of PLHIV, characterized by reduced repertoire diversity and oligoclonal T cell expansion correlated with elevated CD8 T cell counts. We found no evidence that these expansions were driven by cytomegalovirus or another common antigen. Increased frequency of long CDR3 sequences and reduced frequency of public sequences among the expanded clones implicated abnormal thymic selection as a contributing factor. These abnormalities in the repertoire correlated with systems level evidence of persistent T cell activation in genome-wide blood transcriptomes. Conclusions: The diversity of T cell receptor repertoires in PLHIV on long term ART remains significantly depleted, and skewed by idiosyncratic clones, partly attributable to altered thymic output and associated with T cell mediated chronic immune activation. Further investigation of thymic function and the antigenic drivers of T cell clonal selection in PLHIV are critical to efforts to fully re-establish normal immune function.